Larangan Perkawinan Sesuku di Nagari Bungo Tanjuang Kabupaten Tanah Datar Sumatera Barat Ditinjau dari UU No.1 Tahun 1974 tentang Perkawinan - Miftahur Rahmi; Eva Fauziah; Fahmi Fatwa Rosyadi (UNISBA Press, 2022)
Abstract. This research is based on the traditional Minangkabau rules that prohibit tribal marriage. There is no law or verse of the Qur'an that prohibits same marriage. While in minangkabau custom, especially Nagari Bungo Tanjuang upholds falsafat